(untitled) (Global Journal of Management and Business Research, 2022)
Academically the subject of customer-centricity, in the context of the Lebanese market, was not been addressed earlier. The need to identify the factors that drive the success of a customer centric strategy for an organization is intensifying. What is important for every organization is to identify and clearly define the benefit and critical success factors (CSFs) of having the customer as the driver for operations. A customer-centric organization capitalizes on an operating model based on deep understanding of its customers. What do they value, and what contribution they make to the profitability of the company. This paper aims to assess and analyze the critical success factors of organizational customer-centricity within the context of the Lebanese market. The research follows a quantitative approach with data collected from survey questionnaires administered to different employees of different organizations in different Lebanese regions. The analysis of data was carried out to formulate a general proposition about customer-centricity in the Lebanese market. Processing of data was done using the Statistical Product and Process Solution (SPSS). Descriptive and inferential statistics results were reported in different forms including pie charts, t-tests, chi-square tests, cross-tabulation analysis, and regression analysis. The respective findings serve as a general proposition that reflects the objectives of this research. Findings reveal that Lebanese organizations should capitalize on the importance of internal factors such as leadership, culture, and structure during the process of developing a customer-centric strategy. By doing so, those factors will complement other external factors which will ensure the success of this strategy.